THE UTILIZATION OF THERMOVISION MEASUREMENTS AROUND HEAT TRANSFER SURFACES - ČERNECKÝ, Jozef (Trends in education, 2012)
This article concerns the usage of thermovision camera for heat transfer measurement around shaped heat transfer surfaces. Considering the fact, that transparent objects has been used during the measurements, appropriate visualization components must be chosen, which are afterwards recorded using the camera. The thermovision cameras can be advantageously used for teaching subjects that focus on heat transfer and verification of associated calculations or demonstration of heat losses through building constructions.
Keywords: thermovision camera; heat transfer; visualization component.